Aerobic Exercise and Endothelium - D’Almeida, Allan Di Giaimo; Rica, Roberta Luksevicius; Evangelista, Alexandre Lopes; Silva, Ariana A.; Serra, Andrey Jorge; Gama, Eliane F.; Bocalini, Danilo Sales (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: A few years ago, it was believed that the endothelium was just a membrane separating blood from the outermost layers of blood vessels. However, it has now become recognized as a mediator of vasoconstricting and vasodilatory substances, regulating vessel tone through the information received. The main vasodilatory substance released by the endothelium is nitric oxide, a gas responsible for the inhibition of neovascular growth and platelet aggregation, modulating inflammation and coagulation, and can be released through physical and humoral stimuli. Exercise is considered the best non-pharmacological mechanism in the prevention and treatment of cardiovascular diseases, by promoting greater blood flow, generating blood shear forces on the vessel wall and thus releasing nitric oxide, the most important vasodilator produced by the endothelium. Objective: Verify the effects of aerobic exercise on the endothelium. Methods: We reviewed the studies that evaluated the effects of aerobic exercise and its intensities on the endothelium. Results: According to the studies reviewed in this research, impaired endothelial function improves through aerobic training, whether low, moderate or high intensity. Conclusion: Physical activity, specifically aerobic exercise is an important tool in the production of nitric oxide, responsible for blood vasodilation, inhibition of platelet aggregation among other symptoms of endothelial dysfunction.